Using simple telehealth in primary care to reduce blood pressure: a service evaluation. Issue 6 (31st October 2012) - Cottrell, Elizabeth; Chambers, Ruth; O'Connell, Phil
Abstract : Objectives: This service evaluation examines how efficiently an innovative, simple and interactive blood pressure (BP) management intervention improves BP control in general practice. Design: Prospective service evaluation. Setting: Ten volunteer general practitioner (GP) practices in Stoke on Trent, UK. Participants: Practice staff identified 124 intervention patients and invited them to participate based on two inclusion criteria: (1) patient has chronic kidney disease (CKD) stages 3 or 4 with BP persistently >130/85 mm Hg or (2) patient is >50 years-old (without CKD stages 3–5) with BP persistently >140/90 mm Hg despite prescribed antihypertensive medication. Three selected hypertensive control patients per intervention patient underwent usual clinical care (n=364). Interventions: Intervention patients used 'Florence', a simple, interactive mobile phone texting service with BP management intervention for 3 months, or for less time if their BP became controlled. Patients measured their BP, text their readings to Florence, received an immediate automatic response and had results reviewed by their GP/practice nurse at least weekly. Main outcome measures: Baseline data including recent BP readings and medications were collected; similar information was obtained for 6 months for both control and intervention patients. Average BP readings and medication usage were determined. Results: At final data collection, five intervention patients had not yet completed the full programme. Control and intervention patients were well matched except that intervention patients had significantly greater baseline BP. Greatest BP reductions were among hypertensive intervention patients without CKD stages 3–5. Intervention patients had significantly more BP readings and more changes in medication over the 3-month data collection period. Conclusions: Simple telehealth is acceptable and effective in reducing patients' BP. In future, poorly controlled patients could be targeted to maximise BP reductions or broader use could improve diagnostic accuracy and accessibility for patients who struggle to regularly attend their GP surgery.